Education Character in Room Class Social Sciences School Base - Harahap, Silvi Ayundaliani; Amanda, Widya (Journal of Elementary School Education, 2024)
Character Education in Elementary School Social Sciences Classrooms Education is essentially a conscious effort to develop students' potential. Character education is an effort to shape children's character so that they become good human beings, citizens and good citizens. This is to be able to predict the symptoms and long-term development of the crisis that the country will face. Social studies education is a subject that studies social life, the content of which is based on the study of history, geography, economics, sociology, anthropology and national administration.Through social studies learning, character education values can be instilled by integrating these materials into social studies learning.